Activity of Ceruloplasmin in guinea pigs' trachea in late periods of experimental allergic alveolitis development and their correction with thiotriazolin - Mariana Ljubomurivna Baida (Kazimierz Wielki University, 2017)
We have investigated the results of alterations in indices of pro-oxidant (conjugated diene and malondialdehyde ) and antioxidant (ceruloplasmin) systems in guinea pigs' trachea in experimental allergic alveolitis development. The results of our experimental work have showed a significant accumulation of lipid peroxidation products in the trachea`s tissure in late periods ( on 44th and 54th days) . The state of antioxidant defence was characterized by moderate decrease of ceruloplasmin activity. A potential role of oxidative stress in the pathogenesis of allergic alveolitis has been demonstrated. Increased oxidant levels and decreased antioxidant defences can contribute to the progression of this immune comlex pathology. Reduction of conjugated diene and malondialdehyde content and elevation of ceruloplasmin activity have been reported in animals with this experimental model of disease after using of thiotriazolin.